Sequence conservation in field and experimental isolates of Borna disease virus. - Schneider, P A (1994)
Coding and noncoding sequences were analyzed from field and experimental isolates of Borna disease virus. For a 24-kDa protein, maximum divergence was 1.5% at the predicted amino acid level and 3.1% at the nucleotide level. For a 40-kDa protein, maximum divergence was 1.1% at the predicted amino acid level and 4.1% at the nucleotide level. The highest variability in sequence (10%) was found in a 40-nucleotide stretch of genomic RNA between coding sequences for the 40- and 24-kDa proteins. The degree of sequence conservation in these isolates, passaged in various host species in vivo and in vitro over a period of 64 years, is unusual for negative-strand RNA viruses.